REPRESENTASI DAN PESAN MORAL DALAM FILM INDONESIA DANCING IN THE RAIN - Putri Cahya Sufiyah; Farid Pribadi (KRONIK : Journal of History Education and Historiography, 2022)
The existence of several films that carry the theme of disability is expected to build public awareness of the importance of equal rights of minority groups, especially those with disabilities in various fields of life. The existence of misrepresentation can lead to various problems that persons with disabilities will feel. In addition, every film is also equipped with a moral message because human life can not possibly be separated from moral values. This study aims to determine the representation and moral messages of the film Dancing In The Rain. This study used qualitative research methods. This method places more emphasis on descriptive research and emphasizes detailed information analysis. The data analysis technique used is Roland Barthes' semiotic analysis. The data used are primary data and secondary data. Primary data comes from films, meanwhile secondary data comes from literary sources such as journals, articles, theses, books, websites, and other supporting sources. The study's results indicate that in a community, the presence of persons with disabilities is represented as an abnormal or abnormal condition. In particular, there are three moral messages in the film, namely non-discrimination messages, messages of friendship, and messages of sincerity.